2017
DOI: 10.1007/s00394-016-1373-z
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil supplementation attenuates neuroinflammation and alleviates depressive-like behavior in rats submitted to repeated lipopolysaccharide

Abstract: These findings provide novel insights into the antidepressant action of PUFAs and further strengthen the link between inflammation and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 47 publications
5
39
2
Order By: Relevance
“…++ p < 0.01 compared to OVX group cytokines. Meanwhile, in accordance with the findings in the animal models of LPS or stress-induced depression [10], the anti-inflammatory and anti-depressant properties of PUFA were also verified in this OVX model. These beneficial effects are very likely to be associated with the phenotypic transition of microglia, as the present study showed that PUFA supplementation maintained the normal homeostatic balance between the M1 and the M2 phenotypes.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…++ p < 0.01 compared to OVX group cytokines. Meanwhile, in accordance with the findings in the animal models of LPS or stress-induced depression [10], the anti-inflammatory and anti-depressant properties of PUFA were also verified in this OVX model. These beneficial effects are very likely to be associated with the phenotypic transition of microglia, as the present study showed that PUFA supplementation maintained the normal homeostatic balance between the M1 and the M2 phenotypes.…”
Section: Discussionsupporting
confidence: 88%
“…In support, it has been found that PUFA contains robust antidepressant effects in both clinical trials and chronic stress-induced depression-like rodents [23,24]. Additionally, we previously found that PUFA administration mitigates neuroinflammation and depression-like behaviors in animals exposed to repeated LPS challenge [10]. In fact, the antidepressant effect of PUFA is, at least partially, attributed to its immune-modulating actions and the inflammatory progression is tightly linked to the depression-line behaviors caused by either chronic stress, LPS or OVX.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Additionally, nuclear erythroid-related factor 2 (Nrf2) was involved in metabolic homeostasis and inflammation and has become a promising target for the prevention or treatment of depressive disorders. As earlier researches showed that fish oil and conjugated linoleic acid can induce Nrf2 upregulation, their protective ability has been evaluated in a rat model of depression 28,29 . The discovery that the levels of linoleic acid, palmitic acid, stearic acid, oleamide, and palmitoleic www.nature.com/scientificreports www.nature.com/scientificreports/ acid were significantly altered in the CUMS group compared to the control rats may help to understand the molecular mechanisms associated with inflammation and oxidative stress that underlie depression.…”
Section: Discussionmentioning
confidence: 99%